6th International Conference on Modification of Materials with Particle Beams and Plasma Flows: 23-28 September, 2002, Tomsk, Russia proceedings - Mesyats G. A. Gennady Andreyevich; Korovin S. D.; Ryabchikov A. I. Aleksandr Ilyich (Tomsk, Kursiv, 2002)
In memory of Academician of Russian Academy of Sciences Sergey P. Bugaev